Jamstack Performance and Cost-Effective Analysis with Traditional CMS Websites - Permana, Kadek Arya Putra; Suarjaya, I Made Agus Dwi; Wirdiani, Ni Kadek Ayu (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 2 (2022): JITTER, Vol.3, No.2, August 2022, 2022)
Website is a medium that cannot be separated from technological developments, websites are needed because of their practical and easy use, especially a landing page website that is used by business and non-profit people to convey information. The website is developed using a custom-built architecture so that the development and maintenance process runs well. The world is developing faster and faster so that the old website development architecture over time is increasingly difficult to adapt, so there is a new website development architecture, one of which is Jamstack, the Jamstack architecture is said to have advantages over the old architectures that are widely used until now, one of which is LAMP Stack, to ensure the correctness of these arguments, a detailed analysis is needed so as to get results that match the facts.